Heat Shock Protein 70 (Hsp70) Level is Lower in Premature Rupture of Membrane - Muhammad RA Radam; Soetrisno Soetrisno; Supriyadi H Respati (Indonesian Journal of Obstetrics and Gynecology, 2014)
AbstractObjective: To prove wheth er the levels of Heat Shock Protein 70 (Hsp70) was lower in women experiencing premature rupture of membranes than in women with normal aterm pregnancy in order to explain occurrence of pregnancy premature rupture of membranes at termin biomolecular (Hsp70). Method: This was an obse rvational resear ch and the study design was a cross-sectional study. The number of all samples was 60 women, divided into 2 groups and each group contained 30 women. Independ ent var iable: Heat Shock Protein 70 level, Depend ent var iable: Premature Rupture of Membrane. Data was analyzed by t test Result: Based on matern al character istic on both groups, the mean levels of Hsp70 in serum of pr egnant women with PROM lower (0.36) compared to normal pregnant group (3.94) and this difference was statistically significant (p<O.OOl). Diagnostic valu e of the power levels of Hsp 70 in th e PROM compared with norm al pregnancies analysis using Receiver Operating Characteristic curve (ROC) in SPSS17.0 for Windows for by 0.833 or 83.3%, it can be concluded that the diagnostic value of the PROM Hsp70 levels were good (>50%). Conclusion: Theme an levels of Hsp 70 in premature rupture of membranes obtained lower levels than in normal full-term pregnancy and this difference was sta tistically significant. Keywords: Heat Shock Protein 70, maternal stress, PROM